JIDS : A Host-based Intrusion Detection System for GNU/Linux - Andrey Ferriyan (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2015)
Intrusion Detection System (IDS) is applicationwhich monitors system or network anomaly. Based on categorythere are two kinds of IDS, Host-based and Network-based. JibrilIntrusion Detection System (JIDS) is a stand alone Host-basedIDS. JIDS propose file integrity checking for detecting anomalyin system. All binary system will be checked using md5 hash. Ifthe hash doesn't match with the database, it will be marked assuspicious file, logged and should be checked